2019
DOI: 10.1111/pedi.12964
|View full text |Cite
|
Sign up to set email alerts
|

Leptin, adiponectin, and their ratio as markers of insulin resistance and cardiometabolic risk in childhood obesity

Abstract: Background: It is imperative to develop markers for risk stratification and detection of cardiometabolic comorbidities in children with obesity. The adipokines leptin and adiponectin are both involved in fat mass regulation and the development of obesityrelated disorders; furthermore, their ratio (leptin/adiponectin ratio) is suggested to be associated with insulin resistance and cardiometabolic risk.Objective: To evaluate associations between fasting serum concentrations of the adipokines (total leptin and ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
57
1
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(68 citation statements)
references
References 45 publications
4
57
1
6
Order By: Relevance
“…These biological mediators have pro-and anti-inflammatory properties and modulate several physiological functions, such as energy balance, insulin sensibility, inflammatory and immune responses, appetite, and vascular homeostasis [30]. Balance between adipokines is crucial to integrate metabolism with several physiologic functions [13], and proinflammatory adipokines may play a critical role in the progression of chronic inflammation and the development of MS, hypertension, T2D, obesity and CVD [12,13,[31][32][33], even at early ages [15,34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These biological mediators have pro-and anti-inflammatory properties and modulate several physiological functions, such as energy balance, insulin sensibility, inflammatory and immune responses, appetite, and vascular homeostasis [30]. Balance between adipokines is crucial to integrate metabolism with several physiologic functions [13], and proinflammatory adipokines may play a critical role in the progression of chronic inflammation and the development of MS, hypertension, T2D, obesity and CVD [12,13,[31][32][33], even at early ages [15,34].…”
Section: Discussionmentioning
confidence: 99%
“…Reviews focused on the impact of adipose tissue disturbance in the adipokine profile have demonstrated that balance shifts to favor proinflammatory adipokines may play a critical role in the development of cardiometabolic pathologies [12][13][14]. It is known that abnormal adipokine profile may be observed in obese children [15]. Moreover, it was suggested that impaired growth during critical periods, such as in the third trimester of pregnancy can lead the programming of adipose tissue, conferring a high subsequent cardiometabolic risk later in life [16].…”
Section: Introductionmentioning
confidence: 99%
“…TG : HDL-C ratio and triglyceride-glucose index are all reported to be associated with the cardiometabolic disorders [45,46]. Leptin, adiponectin, and their ratio were associated with insulin resistance and other cardiometabolic comorbidities [47]. In the latest researches, branched chain amino acids were found to be passive biomarkers or the key to the pathogenesis of cardiometabolic diseases [48].…”
Section: Journal Of Diabetes Researchmentioning
confidence: 99%
“…Adipokines are cytokines secreted from adipose tissue, which affect a broad spectrum of biological processes (4)(5)(6)(7). Some of these adipokines, such as resistin and leptin, antagonize insulin function in peripheral tissues, especially in the liver and skeletal muscles, which leads to insulin resistance (7)(8)(9)(10). In contrast, adiponectin increases insulin sensitivity (11,12).…”
Section: Introductionmentioning
confidence: 99%